Strategic Analysis of the Transport Infrastructure Development in Saint Petersburg Urban Agglomeration as a Socio-Economic Problem Solving Tool - N. V. Dedyukhina (Учёт. Анализ. Аудит, 2020)
The article is devoted to the study of possible consequences of the implementation of various scenarios for the “Strategy of Social and Economic Development of Saint Petersburg for the period up to 2035”. The authors present the results of the target scenario opportunities and risks analysis and conclude that it is necessary to review the approach adopted by the Government of Saint Petersburg to selecting the target scenario for the city’s development in favor of an updated baseline scenario which takes into account new threats and challenges. The methodological framework of the research is formed on the basis of the strategic analysis concepts. The research methodology involves producing matrices and maps to assess the risk of failure to achieve strategic objectives, matrices to assess conditions and consequences of implementation of the Comprehensive Plan of Transport Service (Comprehensive Plan) in the urban agglomeration. The article determines the priorities in providing sources of funding for participants according to the inertial and customized options of the Comprehensive Plan implementation. The evidence base obtained within the study makes it possible to justify a set of priority preventive measures to minimize the negative consequences of associated risks and threats. Under conditions of resource constraints and growing macro environment risks the Comprehensive Plan becomes the main driver of socio-economic development of the urban agglomeration. The study may be of interest to the representatives of regional state authorities of the Russian Federation, researchers, teachers and managers of educational programs in Economics and Management of higher education institutions.